Study of Freeze-dried Chitosan Beads Encapsulating Live Lactic Acid Bacteria for Removal of Reactive Dyes (Journal of Fiber Bioengineering and Informatics, 2015)
Water pollution by the discharge of dye residue has been polluting the planet for decades. Chitosan is\rone of the natural abundant biomasses that show excellent adsorption toward colorants. Nevertheless,\rsophisticated chemical modifications of chitosan are inevitable to enhance physical and chemical stabilities\rin practical applications. In the present study, simple freeze-drying has been adopted to chitosan (CHI)\rbeads showing good stability at low levels of pH. The results show complete decolourisation of Reactive\rBlue 19 (RB19) within 2 hours at pH 3 and temperature of 37 \u00b0C. The encapsulation of live bacterium\rLactobacillus casei (L. casei) into chitosan beads for dyestuff removal is also evaluated. Kinetics studies\rshow a faster initial rate of adsorption by L. casei-chitosan beads at pH 3 and temperature of 37 \u00b0C.\rThe adsorptions partially follow the intraparticle diffusion mechanism.
Keywords: Chitosan Beads; Freeze-drying; Lactobacillus Casei; Reactive Blue 19; Removal